Evaluation of high-dose cytarabine in induction therapy for children with de novo acute myeloid leukemia: a study protocol of the Japan Children's Cancer Group Multi-Center Seamless Phase II–III Randomized Trial (JPLSG AML-12). (28th April 2018) - Tomizawa, Daisuke; Tanaka, Shiro; Hasegawa, Daisuke; Iwamoto, Shotaro; Hiramatsu, Hidefumi; Kiyokawa, Nobutaka; Miyachi, Hayato; Horibe, Keizo; Saito, Akiko Moriya; Taga, Takashi; Adachi, Souichi
Abstract : We are conducting a multi-center trial in Japan, which is a seamless Phase II–III study in previously untreated, newly diagnosed patients with acute myeloid leukemia at <18 years of age. Abstract: The purpose of this study is to compare the efficacy and safety of combination therapy (HD-ECM) including high-dose cytarabine in initial induction therapy with that of combination therapy (ECM) involving the continuous administration of cytarabine for previously untreated, newly diagnosed patients with AML at <18 years of age. This is a seamless Phase II–III clinical trial, consisting of Phase II and III parts. In the Phase II part, the safety of the experimental treatment (HD-ECM) will be examined. Subsequently, the Phase III study will compare the efficacy and safety of HD-ECM with that of standard ECM. The primary endpoint of the Phase II study is the early mortality rate. The primary endpoints of the Phase III study are the 3-year event-free survival rate and the positive minimal residual disease rate by flow cytometry after initial induction therapy. This trial has been registered at the UMIN Clinical Trials Registry (UMIN000013288).